Dynamical behavior of the ice sheet in Mizuho Plateau, East Antarctica - Nishio, Fumihiko; Mae, Shinji; Ohmae, Hirokazu; Takahashi, Shuhei; Nakawo, Masayoshi; Kawada, Kunio (National Institute of Polar Research, 1989)
P(論文) The Japanese Antarctic Research Expedition (JARE) has continued glaciological work in Mizuho Plateau, East Antarctica. We have already reported that the ice sheet on Mizuho Plateau which flows into Shirase Glacier, classified as a fast-moving outlet glacier, was thinning at a rate of about 70cm・a^<-1> and the profile of basal shear stress along the central flow line derived from topographic map was similar to that of surging glaciers. A new 5-year glaciological program in Mizuho Plateau and East Queen Maud Land which started in 1981 is now being carried out. We have obtained new results as follows : (1) The ice sheet in the downstream region where ice elevation is lower than about 2800m is thinning, based upon data on horizontal and vertical flow velocity, strain rate, inclination of ice surface, accumulation rate and densification of snow. (2) The result of the radio-echo sounding on Mizuho Plateau suggests that the base of the ice sheet in the downstream region is wet. Based upon a two-dimensional numerical model, the calculated bottom temperature shows that the ice temperature at the base of the ice sheet in the glacier downstream is at the pressure melting point and the ice base is also wet. These results supports the result described in (1), since basal sliding due to the wet base causes the ice sheet thinning as proposed by our previous studies. Summarizing these results, a possible explanation of ice sheet variation on Mizuho Plateau is as follows : the thinning of the ice sheet caused by the basal sliding due to melting of the ice base started at the mouth of the Shirase Glacier and has been expanding upstream to reach the present state. A simple calculation, using flow velocities, shows that the thinning started at Shirase Glacier about a few thousand years ago. departmental bulletin paper